2012
DOI: 10.1177/0363546512449618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Phosphate–Hybridized Tendon Graft in Anterior Cruciate Ligament Reconstruction

Abstract: Background: The authors developed a novel technique to improve tendon-bone healing by hybridizing calcium phosphate (CaP) with a tendon graft using an alternating soaking process. Hypothesis: Anterior cruciate ligament (ACL) reconstruction using the CaP-hybridized tendon graft would have a better clinical outcome and reduce the percentage of bone tunnel enlargement compared with a conventional method because of the enhanced anchoring between the tendon graft and the bone. Study Design: Randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
0
34
1
2
Order By: Relevance
“…During this process, mechanical and biological factors are involved in the healing process of the reconstructed tendons [25][26][27][28][29]. In the distal part of the bone tunnel, the mechanical effect was relatively low and the graft-bone healing was influenced mainly by the biological environment.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, mechanical and biological factors are involved in the healing process of the reconstructed tendons [25][26][27][28][29]. In the distal part of the bone tunnel, the mechanical effect was relatively low and the graft-bone healing was influenced mainly by the biological environment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to allow patients return to sports in an early time, there is a critical need for promoting graft osseointegration early after ACL reconstruction . Although several bioactive materials, like hyaluronic acid or cationized gelatin, can enhance surface biaoctivity of the PET grafts, the rates of graft osseointegration are still quite slow .…”
Section: Discussionmentioning
confidence: 99%
“…However, this method can be used only for autograft transplantation and not FDP tendon reconstruction because of unavailability of intrasynovial autograft for calcification. Mutsuzaki et al also developed a calcium phosphate–hybridized tendon graft and reported positive results after transplantation, but the graft did not show graded minerals inside the tendon. In the current study, a graded mineral deposition zone was generated inside the tendon by using a previous established method .…”
Section: Discussionmentioning
confidence: 99%